Diverse Presentation of Secondary Aortoenteric Fistulae. (29th December 2011) - Simon, Tracey; Feller, Edward
Abstract : Secondary aortoenteric fistula, due to mechanical erosion or infection of a prosthetic graft, is a very rare cause of gastrointestinal bleeding and an uncommon complication of abdominal aortic aneurysm repair. A retrospective chart review conducted at our institution revealed 5 cases of secondary AEF occurring between 2006 and 2010. Presentations were diverse, including hematemesis, coffee-ground emesis, and unexplained sepsis. Delay in diagnosis was common. In reporting these cases, we seek to highlight the diverse clinical spectrum and potentially misleading features of this condition. Clinicians must retain a high index of suspicion to avoid potentially catastrophic outcomes.